ENTREPRENEURSHIP IN THE FIELD OF INDONESIAN LANGUAGE FOR FOREIGN SPEAKERS THROUGH EDUCATIONAL GAMES AND YOUTUBE - Episitrepo Lawolo; Agustina; Jamaluddin Nasution (Rahis Cendekia Indonesia, 2026)
The development of entrepreneurship in the field of Indonesian Language Learning for Foreign Speakers (BIPA) has strategic potential in expanding cultural diplomacy, increasing educational competitiveness, and opening up opportunities for language-based creative economies. This study aims to examine the integration of digital innovation through the development of story-based educational games and the use of the YouTube platform as a means of producing and distributing BIPA educational content. Educational games are developed to provide an immersive, interactive, and contextual learning experience that can increase motivation, learning outcomes, and the involvement of foreign students in Indonesian culture. Meanwhile, YouTube digitalization is utilized as a medium for entrepreneurship in the field of Indonesian Language and Literature Education (PBSI) by presenting learning content, linguistic tutorials, culture, and creative materials that have both educational and economic value. Through a qualitative-descriptive approach and digital market potential analysis, this study shows that the integration of educational games and YouTube not only enriches the BIPA learning model but also opens up business opportunities for educators, content creators, and learning media developers. In conclusion, this digital innovation contributes to strengthening an adaptive, creative, and sustainable Indonesian language edupreneurship ecosystem.